Localized scleroderma in adults and children. Clinical and laboratory investigations on 239 cases - Marzano, Angelo V; Menni, Silvano; Parodi, Aurora; Borghi, Alessandro; Fuligni, Alessandra; Fabbri, Paolo; Caputo, Ruggero (EJD. European journal of dermatology, 2003)
We examined, retrospectively, 239 patients (113 adults and 126 children) with LS, referred to our department from 1980 up to 2001. Clinical parameters evaluated were age, sex, LS variant, extracutaneous manifestations, duration of disease and follow-up. We also considered laboratory findings, most notably erythrocyte sedimentation rate, blood eosinophilia, antinuclear antibodies (ANA) and various circulating autoantibodies. Plaque morphea was the most common form in both groups (74 adults and 61 children). In contrast, linear scleroderma affected children much more frequently than adults (22 children vs 7 adults). When the limbs were involved, this variant could lead to severe orthopedic complications (10 children vs one adult patient). On the other hand, linear scleroderma of the scalp and face comprising scleroderma en coup de sabre and Parry-Romberg syndrome was also more frequent in children (14 children vs 5 adults) causing ocular (8 cases), oral (7 cases) and neurologic (8 cases) abnormalities. Typical of childhood were mixed forms (18 pediatric patients), characterized by combination of different LS variants, which usually followed a more protracted and complicated course and showed ANA positivity (11 cases). Among adults, Raynaud's phenomenon was found in 8 patients; interestingly, anticentromere antibodies were detected in 4 of these subjects, identifying a subset at risk for progression to systemic disease. Children and adults developed LS with analogous clinical and immunological features. However, the prevalence of LS variants differed between adult and pediatric populations, leading to different extracutaneous complications.